Volcanic gas monitoring of quiescent volcanoes using permanent Multi-GAS networks - AIUPPA, Alessandro; TAMBURELLO, Giancarlo; DI NAPOLI, Rossella; Liuzzo,M; Giudice, G; Bergsson, B; Ilyinskaya,E; Papazachos, C; Vougioukalakis, G; Francofonte, V. (2014)
The Multi-component Gas Analyzer System (Multi-GAS) has recently consolidated as a standard technique for the nearly real-time in-situ observation of major volcanogenic components (H2O, CO2, SO2, H2S,H2) in volcanic gas plumes. The Multi-GAS has been initially operated at open-vent volcanoes, where it has revealed ideal for long-term continuous observations at for instance Etna and Stromboli volcanoes in Italy, therein paving the way to the acquisition of unprecedentedly long and continuous volcanic gas time-series. We here initially review the present state of the expanding network of permanent Multi-GAS instruments, now covering about 10 volcanoes worldwide. We then specifically focus on the results acquired via Multi-GAS monitoring of fumarolic activity at two quiescent, but potentially hazardous volcanoes in Europe: Santorini, in Greece, and Hekla, in Iceland. Our results overall demonstrate the potential of the Multi-GAS in the monitoring of even sluggish, weak fuming hydrothermal activity as currently observed at both Santorini and Hekla. Quantitative modeling of the results open the way to charactering magmatic-hydrothermal and gas-groundwater interactions with unprecedented detail. We show that, at both volcanoes, gas compositions range in time from H2O-rich (H2O/CO2 > 1) to CO2-dominated and S-poor (CO2/H2S > 10,000), a compositional trend which we quantitatively reproduce via model runs of gas-water-rock interactions initialized using EQ 3/6.